Effect of Organo‐Modified Nanosepiolite on Fire Behaviors and Mechanical Performance of Polypropylene Composites. Issue 2 (14th January 2015) - Zhang, Junhao; de Juan, Sergio; Esteban‐Cubillo, Antonio; Santarén, Julio; Wang, De‐Yi
Abstract The objective of the study was to investigate the effect of the organo‐modified nanosepiolite (ONSep) on improving the fire safety of polypropylene (PP). The composites based on PP, flame retardant master batch (MB‐FR, 25 wt% PP+50 wt% decabromodiphenyl ether (DBDPE)+25% antimony trioxide (ATO)) and ONSep were prepared via melt blending. The results of the limiting oxygen index (LOI) and vertical burning rating (UL‐94) test indicated that PP/40 wt% MB composites had no rating with seriously dripping phenomenon, while the LOI value was only 22.5. However, as 4 wt% ONSep was added in PP/40 wt% MB composites, the composites achieved UL94 V‐0 rating and the LOI value was 24.3. In comparison, PP/50 wt% MB composites could not reach the V‐0 rating either. The TGA results revealed that the addition of ONSep enhanced the thermal stability of the PP/MB‐FR composites. The cone calorimeter results indicated that the heat release rate, average mass loss rate, smoke production rate and smoke temperature of the PP/40 wt% MB‐FR/4 wt% ONSep composites decreased in comparison with those of PP/40 wt% MB‐FR composites. Simultaneously, the Young modulus and impact strength were also much better improved with the increase of ONSep loading. Therefore, the synergistic flame retardancy of ONSep in PP/MB‐FR matrix significantly containing a halogen based flame retardant (DBDPE) significantly improved the fire safety and mechanical properties of the composites, and allowed to decrease the total amount of brominated fire retardants.